Spraying corn oil on Mute Swan Cygnus olor eggs to prevent hatching - Hindman, Larry J.; Harvey, IV, William F.; Conley, Linda E. (Wildfowl, 2014)
During the 1980s and 1990s, non-native Mute Swans Cygnus olorincreased dramatically in the Maryland (USA) portion of the Chesapeake Bay. As a method to slow further population growth, we tested the effectiveness of coating eggs in incubation with 100% food-grade corn oil to prevent hatching. During April to June 1996 and 1997, hatching success and nest abandonment was monitored in 26 control and 28 treatment nests. Whereas all full-term control nests hatched at least one egg, with an overall hatching success of 82.8% (111/134 eggs in 22 nests), no eggs in treated nests (0/118 eggs in 19 nests) hatched. Abandonment of oiled nests did not differ from that of controls, nor did abandonment among treated nests differ from controls between those treated early (first half of incubation) or late (last half of incubation). Treated nests carried full term were incubated on average an additional 16 ± 2.63 days (mean ± s.e.) beyond estimated hatching date. These experimental results were applied to a large-scale, integrated control programme initiated by the Maryland Department of Natural Resources (MDNR) aimed at reducing Mute Swan numbers in Maryland. In 2002, a fact sheet about the deleterious effects of Mute Swans and the agency’s plan to treat nests was mailed to > 4,000 shoreline property owners who had previously licensed offshore waterfowl hunting blinds. Property owners who had known Mute Swan nests on their lands were contacted to seek multiple year permission to access their property to oil swan eggs. Over a 13-year period (2002–2003, 2005–2014), 1,689 Mute Swan nests containing 9,438 eggs were treated. Egg treatment was especially effective in reducing the number of swans that required culling by preventing an estimated additional c. 6,200 Mute Swans from entering the non-breeding population. Egg treatment was combined with the culling of adult swans (2005–2013) as part of the MDNR control programme that resulted in a reduction of the non-native Mute Swan population from c. 3,995 in 1999 to c. 41 in 2014. Corn oil provides resource managers with an effective, nontoxic method of reducing Mute Swan hatching success. While egg oiling can reduce the production of cygnets, however, merely treating eggs does little to reduce the swan population. If managers desire to reduce a Mute Swan population quickly (< 5–10 years), an integrated strategy of treating swan nests and culling swans (i.e. reducing annual survival) by humane lethal means should be considered.